1993
DOI: 10.1002/j.1537-2197.1993.tb15238.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Dna Evidence for the Interrelationships of Tomatoes, Potatoes, and Pepinos (Solanaceae)

Abstract: We used chloroplast DNA restriction site analysis to test hypotheses of relationships of Solarium subgenus Potatoe (including potatoes and pepinos), two other Solanum, Cyphomandra (the tree tomatoes), and Lycopersicon (the tomatoes). Capsicum and Datura were used as outgroups. The results support two main clades among the taxa we studied: 1) Solanum subgenus Potatoe and Lycopersicon; and 2) other Solanum and Cyphomandra. Within the first clade, the following groups were supported: a) sect. Basarthrum and sect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
3
6

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 238 publications
(158 citation statements)
references
References 67 publications
6
130
3
6
Order By: Relevance
“…Although the former genus Lycopersicon has been taxonomically reassigned to Solanum section Lycopersicon (Spooner et al 1993;Peralta and Spooner 2001), we will retain the old nomenclature for consistency with our and other authors' previous work. Native to western South America, wild tomatoes are herbaceous perennials, with individual plants often bearing receptive, insect-pollinated flowers and fruits simultaneously.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Although the former genus Lycopersicon has been taxonomically reassigned to Solanum section Lycopersicon (Spooner et al 1993;Peralta and Spooner 2001), we will retain the old nomenclature for consistency with our and other authors' previous work. Native to western South America, wild tomatoes are herbaceous perennials, with individual plants often bearing receptive, insect-pollinated flowers and fruits simultaneously.…”
Section: Methodsmentioning
confidence: 90%
“…Taxonomic studies based on a variety of molecular markers have identified either S. lycopersicoides or S. ochranthum as the sister group to the tomato clade (Spooner et al 1993(Spooner et al , 2005Peralta and Spooner 2001). The estimated divergence time between S. ochranthum and Lycopersicon is between 5.8 and 18.6 million years (Rose 2002), while the divergence time between S. lycopersicoides and Lycopersicon has not been estimated.…”
Section: Methodsmentioning
confidence: 99%
“…The pepino is evolutively linked to the tomato (Spooner et al, 1993) and the growing techniques commonly used for tomato can be used for pepino cultivation. Cultivation of this fruit is possible in temperate conditions (Samuels, 2013) as long as winter protection is provided, or the crop is grown as an annual but pepino needs more time to mature than other widely known Solanaceae vegetable crops, such as the tomato, pepper and eggplant, and in many seasonal climates the summer season is not long enough for this crop; as a consequence, in many cases, pepinos are grown as a greenhouse crop.…”
Section: IVmentioning
confidence: 99%
“…1). Thus, among the taxa comprising subgenus Potatoe, section Juglandifolium and subsection Lycopersicoides are supported as the most closely related and probably ancestral to the tomatoes, subsection Lycopersicum (Child, 1990;Spooner & al., 1993;Peralta & Spooner, 2001).…”
Section: Sectionmentioning
confidence: 99%
“…(Child, 1990; Table 1). Recent phylogenetic analysis using chloroplast DNA (cpDNA) restriction site data revealed that section Juglandifolium Child and subsection Lycopersicoides Child constitute two separate monophyletic groups, sister to the tomatoes (Spooner & al., 1993; (1990). Only the eight sections in the "Tuberarium" relationship are shown.…”
mentioning
confidence: 99%